Two examples of non strictly convex large deviations - De,Marco S; Jacquier,A; Roome,P (Electronic Communications in Probability, 2016)
We present two examples of a large deviations principle where the rate function is not strictly convex. This is motivated by a model used in mathematical finance (the Heston model), and adds a new item to the zoology of non strictly convex large deviations.